Associations of weight-adjusted-waist index and systemic immune-inflammatory index with sKlotho: evidence from the NHANES 2007-2016 - Yang, Mingming; Xu, Qiong; Huang, Linjuan; Zhu, Luqian (Frontiers in Endocrinology, 2025)
BackgroundKlotho is an anti-aging protein, and obesity and inflammation have been identified as having a relationship with Klotho. This study investigated the correlation between weight-adjusted-waist index(WWI), systemic inflammation index(SII) and soluble Klotho (sKlotho) and explored the potential mediating role of SII.MethodsThe association between WWI, SII, and sKlotho was investigated using weighted multivariate linear regression, subgroup analysis, and smoothed curve fitting in this cross-sectional study, which was based on NHANES data. The Bootstrap method was used to test for mediation effects. Covariate selection was validated using the variance inflation factor (VIF).ResultsThe study involved a total of 9,506 participants. The results showed that WWI (β=-0.03; 95%CI:-0.04,-0.01; p<0.0001) was associated with SII (β=-0.00, 95%CI:-0.00,-0.00:p<0.001) and Ln-sKlotho.There was a negative correlation between both WWI and SII and sKlotho. Subgroup analysis showed that gender, age, education, marital status, family income, HEI, PA, hypertension, diabetes, CKD, alcohol use, smoking, and SII did not affect the negative correlation between WWI and sKlotho (FDR-corrected p>0.1). The mediation analysis showed that SII played a significant mediating effect in the role of WWI on sKlotho, with SII mediating 6.78% of the relationship between WWI and sKlotho.ConclusionThere is a negative correlation between WWI and sKlotho, and SII may be an important mediator between WWI and sKlotho. Reducing inflammatory conditions in obese populations may increase sKlotho levels, which in turn may delay organismal aging in middle-aged and elderly people.